Aging-related rotenone-induced neurochemical and behavioral deficits: role of SIRT2 and redox imbalance, and neuroprotection by AK-7 - Wang X; Guan Q; Wang M; Yang L; Bai J; Yan Z; Zhang Y; Liu Z (Dove Medical Press, 2015)
Xijin Wang,1 Qiang Guan,2 Meihua Wang,1 Liu Yang,1 Jie Bai,1 Zhiqiang Yan,3 Yuhong Zhang,4 Zhenguo Liu11Department of Neurology, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, 2Department of Neurology, Tongji Hospital, Tongji University, 3Shanghai Laboratory Animal Center, Chinese Academy of Sciences, 4Department of Neurology, Shanghai Tenth People’s Hospital, Tongji University, Shanghai, People’s Republic of ChinaAbstract: Aging is one of the strongest risk factors for Parkinson’s disease (PD). SIRT2 has been implicated in the aging process. It is pertinent to investigate the role of SIRT2 in aging-related dopaminergic neurotoxicity and to develop effective therapeutic strategies for PD through the use of aging animals. In this study, we observed that rotenone induced significant behavior abnormality and striatal dopamine depletion in aging rats, while it did not do so in young rats. No significant change in striatal serotonin level was observed in the aging rats after rotenone administration. There was also aging-related rotenone-induced increase in substantia nigra (SN) SIRT2 expression in the rats. In addition, there was aging-related rotenone-induced SN malondialdehyde (MDA) increase and glutathione (GSH) decrease in the rats. No significant changes in cerebellar SIRT2, MDA, or GSH levels were observed in the aging rats after rotenone administration. Striatal dopamine content was significantly inversely correlated with SN SIRT2 expression in the rats. AK-7 significantly diminished striatal dopamine depletion and improved behavior abnormality in the rotenone-treated aging rats. Furthermore, AK-7 significantly decreased MDA content and increased GSH content in the SN of rotenone-treated aging rats. Finally, the effect of AK-7 on dopaminergic neurons and redox imbalance was supported by the results from primary mesencephalic cultures. Our study helps to elucidate the mechanism for the participation of aging in PD and suggests that SN SIRT2 may be involved in PD neurodegeneration, that AK-7 may be neuroprotective in PD, and that maintaining redox balance may be one of the mechanisms underlying neuroprotection by AK-7. Keywords: Parkinson’s disease, environmental toxin, dopamine, oxidative stress, sirtuin